Handphone Selection Decision Support System Using Analytical Hierarchy Process Method - Bella Yuristika Fauji; Muhamad Muslihudin; Dedi Irawan (Journal of Intelligent Business and Technology Science (JIBTec), 2022)
Current technological advances are increasingly rapid and very modern especially in the IT field. Making the NB Cell counter often has difficulty in helping consumers to determine the type and type of mobile phone because many brands and prices are offered, to make it easier for users to choose the type of mobile phone to make a decision support system according to the data obtained at the N’B Cell counter. Data collection used in this study includes observation and interview methods at the N'B Cell counter, after the data obtained methods used the AHP (Analytical Hierarchy Process) method, to determine the decision support system using PHP and Mysql as a database. For system design, three main criteria are needed, namely price, specifications, design. This study produces information in the form of an order of priority priorities for mobile phone selection, the result of comparison of values between alternatives using the analytical hierarchy process method. The simulation results that have been done obtained an alternative priority sequence with the acquisition of Xiaomi priority values with priority values of 19%, Oppo 17%, Vivo 19%, Samsung 28% and Nokia 15%. then the recommended cellphone in decision making is Samsung with the first priority of 28%. Users of this system must know about the problems of criteria and alternatives as well as knowledge about AHP for decision making on handphone selection using the AHP method